2010
DOI: 10.1590/s0100-15742010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Práticas institucionais e inclusão escolar

Abstract: No Brasil a concepção de Educação Inclusiva é fortemente marcada pela noção de Educação Especial e pela categorização do comportamento dos alunos. O documento sobre a Política nacional de educação especial na perspectiva da educação inclusiva, entregue ao Ministro da Educação em 7 de janeiro de 2008, acentua as noções de transtorno global ou funcional, de deficiência e de déficit que acompanha este tipo de categorização. Vemos se desenhar nesse documento uma "psicopatologia da inclusão". Pela formulação de doi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
5
0
4
Order By: Relevance
“…In addition to the aspects mentioned above, there aren't always resource rooms with assisted technology, demanded by law, that meet the plurality of these new students promoting self-esteem, autonomy, and creativity. This happens due to the difficulty to implement them and to keep them, considering the number of SNS enrolled in the units (31) .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aspects mentioned above, there aren't always resource rooms with assisted technology, demanded by law, that meet the plurality of these new students promoting self-esteem, autonomy, and creativity. This happens due to the difficulty to implement them and to keep them, considering the number of SNS enrolled in the units (31) .…”
Section: Resultsmentioning
confidence: 99%
“…The present results revealed that different cultural and social factors, also related to the life experiences, may influence the social attitudes. These attitudes may be learned and thus they may be changed, and the essentially characteristic determinants of social attitudes are cognitive (beliefs and opinions), affective (in favor of or against the attitudinal object) and behavioral (with predisposition to action, being a combination of the two former aspects, and that lead to a certain behavior) 25 . Usually, there is agreement between these three components, and when there is a change in one of them, there are processes to restore this agreement, leading to an attitudinal reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…Any change in some of these three components may change the others, since the entire system is triggered when one component is altered. Consequently, a new information, new experience, or new behavior adopted to meet the social norms or when facing another type of agent that may lead to such behavior, may create a state of unconsciousness between the three attitudinal components, leading to a change in attitude 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Na análise dos 47 artigos localizados com a palavra-chave deficiência destacam-se: o estudo de Nabuco (2010), que parte do referencial teórico da psicanálise lacaniana; Caiado e Laplane (2009), que confrontam o discurso oficial com as práticas sociais de exclusão educacional e social, com a finalidade de compreender os rumos da implementação da política inclusiva; Plaisance (2010) discute a relação entre ética, deficiência e inclusão; e Ferreira (2007) objetivou formular e analisar conhecimentos a respeito da inclusão escolar e constatou que não é impossível promover mudanças para implementar uma educação inclusiva que atenda a todos os alunos -trata-se, então, de um desafio superável. Jurdi e Amiralian (2006) tiveram como objetivo compreender interferências e modificações de atividades propostas pela terapia ocupacional nas relações estabelecidas com os alunos com deficiência mental.…”
Section: Análiseunclassified